Struttura e descrizione dei Quaderni del carcere - Francioni, Gianni (International Gramsci Journal, 2023)
This is the Italian guide to Gramsci’s Prison Notebooks, designed initially for an exhibition in Cesena in Italy’s Emilia Romagna region, in which the Notebooks were on show. The guide illustrates their structure, lists the general contents of each of them and, as far as possible, indicates why given notes are found in given sections of the Notebooks, often special sections set aside on purpose, sometimes with Gramsci’s own titling, for second draftings. Such notebook titles and section sub-titles, if in italics, are Gramsci’s own; otherwise they are additions by subsequent editors. Particular attention is paid to the division between miscellaneous, special and translation notebooks; the article includes the most up-to-date information available on when and where each notebook was written.